2002
DOI: 10.1038/sj.hdy.6800070
|View full text |Cite
|
Sign up to set email alerts
|

FISH mapping of 18S-28S and 5S ribosomal DNA, (GATA)n and (TTAGGG)n telomeric repeats in the periwinkle Melarhaphe neritoides (Prosobranchia, Gastropoda, Caenogastropoda)

Abstract: Spermatocyte chromosomes of Melarhaphe neritoides (Mollusca, Prosobranchia, Caenogastropoda) were studied using fluorescent in situ hybridization (FISH) with four repetitive DNA probes (18S rDNA, 5S rDNA, (TTAGGG) n and (GATA) n ). Single-colour FISH consistently mapped one chromosome pair per spread using either 18S or 5S rDNA as probes. The telomeric sequence (TTAGGG) n hybridized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…In addition, the same technique with biotinlabelled (TTAGGG) n and digoxigenin-labelled 18S-28S rDNA probes revealed that ribosomal and telomeric signals were adjacent. A similar configuration has been observed in a periwinkle (Colomba et al, 2002) and a slug (Vitturi et al, 2004). Among vertebrates, an adjacent disposition between telomere and NORs has been reported to be an unusual finding (Liu & Fredga, 1999).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, the same technique with biotinlabelled (TTAGGG) n and digoxigenin-labelled 18S-28S rDNA probes revealed that ribosomal and telomeric signals were adjacent. A similar configuration has been observed in a periwinkle (Colomba et al, 2002) and a slug (Vitturi et al, 2004). Among vertebrates, an adjacent disposition between telomere and NORs has been reported to be an unusual finding (Liu & Fredga, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Among vertebrates, an adjacent disposition between telomere and NORs has been reported to be an unusual finding (Liu & Fredga, 1999). However, this condition occurs more frequently in invertebrates than in vertebrates (Colomba et al, 2002). Nevertheless, the significance of the telomere within NORs is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sinteny or even a close ligation of the18S-28S and 5S rDNA is not a rare phenomenon in animals (e.g. Drouin 1999;Colomba et al, 2002;Vitturi et al, 2002), the most frequent situation is that the two types of rDNA map on different chromosomes (e.g. Wimber & Steffensen, 1970;Matsuda et al, 1994;Kost et al, 1995;Martins & Galetti, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The 5S rRNA genes have been primarily mapped in fish [Martins and Galetti, 1999;Martins and Wasko, 2004;Pisano and Ghigliotti, 2009], and the histone genes have been mapped in a few species, for example in mammals, amphibians, fish, mollusks, and some insects [Graves et al, 1985;Tripputi et al, 1986;Turner et al, 1988;Hankeln el al., 1993;Pendás et al, 1994;Ranz et al, 2003;Zhang et al, 2007;Cabrero et al, 2009;Cabral-de-Mello et al, 2010a, 2011a. These multigene families can be organized in separated clusters or can be associated, as has been described for example in arthropods, annelids, mollusks, and fish [Andrews et al, 1987;Drouin et al, 1987Drouin et al, , 1992Barzotti et al, 2000;Vitturi et al, 2002;Colomba et al, 2002;Eirín-López et al, 2004;Vitturi et al, 2004;Pisano and Ghigliotti, 2009;Cabral-de-Mello et al, 2010a, 2011a.…”
mentioning
confidence: 99%